Digital Payment Infrastructure and Household Consumption Growth: Evidence from QRIS and BI FAST in Indonesia - Faridah; Herminawaty Abubakar; Thanwain; Sitti Mujahida Baharuddin (Global Review of Tourism and Social Sciences, 2026)
This study examines whether the expansion of digital payment infrastructure stimulates household consumption growth in Indonesia. Using a balanced provincial panel covering 2019 to 2024, it estimates the effects of QRIS merchant density and BI FAST exposure on real household consumption per capita through a fixed effects model that controls for regional heterogeneity, macroeconomic shocks, internet penetration, financial depth, economic structure, urbanisation, inflation, and population. The results indicate that greater QRIS merchant density significantly increases household consumption, with stronger effects in provinces characterised by higher informal employment and service sector activity. BI FAST further strengthens consumption growth in regions with greater initial banking access, suggesting that faster and lower cost interbank transfers improve liquidity circulation. These findings demonstrate that payment system modernisation promotes domestic demand in addition to advancing financial inclusion. The study provides new subnational evidence that investments in interoperable digital payment infrastructure can support household consumption, MSME development, and broader macroeconomic policy objectives.